simplify 9/10÷ 3

Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

# simplify 9/10÷ 3

fractions and integers

## Research, Knowledge and Information :

Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

### Simplify radical,rational expression with Step-by-Step Math ...

Simplifying Polynomials. In section 3 of chapter 1 there are several very important definitions, which we have used many times. Since these definitions take on new ...

### Simplifying Fractions - Math Is Fun

Simplifying Fractions. To simplify a fraction, divide the top and bottom by the highest number that can divide into both numbers exactly. Simplifying Fractions

### 3 Ways to Simplify Algebraic Expressions - wikiHow

How to Simplify Algebraic Expressions. Learning how to simplify algebraic expressions is a key part of mastering basic algebra and an extremely valuable tool for all ...

### Section 10.3 Multiplying and Simplifying Radical Expressions

Section 10.3 Multiplying and Simplifying Radical Expressions I. Product Property A. If x and y are any non-negative real numbers, then: xy =x y B.

### How do you simplify 9/10 - 4/5? | Socratic

How do you simplify #9/10 - 4/5#? Algebra Properties of Real Numbers Addition of Rational Numbers. 1 Answer ? 1 Parzival S ...

### Simplify 3/10 to the simplest form - CoolConversion.com

Simplify 3/10 to the simplest form. Here is the answer to questions like: Simplify 3/10 to the simplest form or how to simplify/reduce this fraction: 3/10?

### Simplify any Algebraic Expression - WebMath

Simplify any Algebraic Expression. If you have some tough algebraic expression to simplify, this page will try everything this web site knows to simplify it.

### Can 9 over 10 be simplified - Answers.com

Can 9 over 10 be simplified? ... The only factors of 9 are 3,9, and 1. 1 will not help you simplify, and 25 is not divisible by either 3 or 9.

## Suggested Questions And Answer :

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### sqrt(3a+10) = sqrt(2a-1) + 2

sqrt(3a+10)=sqrt(2a-1)+2 To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(3a+10))^(2)=(~(2a-1)+2)^(2) Simplify the left-hand side of the equation. 3a+10=(~(2a-1)+2)^(2) Squaring an expression is the same as multiplying the expression by itself 2 t

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Fac

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### (13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### (8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### what is the answer for x/7+4=x/7

(x)/(7)+4=(x)/(7) Multiply each term in the equation by 7. (x)/(7)*7+4*7=(x)/(7)*7 Simplify the left-hand side of the equation by canceling the common terms. x+28=(x)/(7)*7 Simplify the right-hand side of the equation by simplifying each term. x+28=x Since x contains the variable to solve for, m

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### Write out the solution to the equation : x + y - z = 0, 2x + 4y - z = 0 and 3x + 2y + 2z = 0

first equation: x + y - z = 0 x + y = z in the other 2 equations, replace z with x + y: 2x + 4y -(x+y) = 0 3x + 2y +2(x+y) = 0 simplify: 2x + 4y -x -y = 0 3x + 2y +2x +2y = 0 simplify more: x + 3y = 0 5x + 4y = 0 in the top equation, move the 3y to the other side: x = -3y in the bottom

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### find a particular solution (e^x+y +ye^y)dx+(xe^y -1)dy=0 if y(0)=-1

This has the form of an exact DE. Let's see if it is.  First rewrite: (e^x+y+ye^y)+(xe^y-1)dy/dx=0=A(x,y)+B(x,y)dy/dx=0 where A=e^x+y+ye^y and B=xe^y-1. (p.d.=partially differentiate; wrt=with respect to)   Take A and p.d. wrt y=1+ye^y+e^y (a) Take B and p.d wrt x=e^y (b) S

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### simplify 6x/x+3=9/x-3-15/x^2-9

6x / (x + 3) = [9 / (x - 3)] - [15 / (x^2 - 9)] 6x(x - 3) / (x + 3)(x - 3) = [9(x + 3) / (x + 3)(x - 3)] - [15 / (x^2 - 9)] (6x^2 - 18x) / (x^2 - 9) = [(9x + 27) / (x^2 - 9)] - [15 / (x^2 - 9)] 6x^2 - 18x = 9x + 27 - 15 6x^2 - 18x - 9x - 12 = 0 6x^2 - 27x - 12 = 0

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how would you simplify this expression (1/y)+(2/7)-(3/2y^2)

(1/y) +(2/7) -(3/2y^2)=0 multipli bi y^2...y +(2/7)y^2 -(3/2)=0 or 14*(2/7)y^2 +14y -14*(3/2)=0 4y^2 +14y -21=0 or (x-1.1331406)(x+4.6331406)=0

#### Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
• Start your question with What, Why, How, When, etc. and end with a "?"
• Be clear and specific
• Use proper spelling and grammar